TRAINING IN MAKING POWTOON-BASED LEARNING MEDIA IN EDUCATION 4.0 - Elly Sukmanasa; Lina Novita; Aries Maesya (International Journal of Business, Economics, and Social Development, 2020)
The role of the teacher is needed to help students in the learning process so that the material can be understood optimally. A teacher is not just teaching in front of the class, but must be able to inspire students. The process of implementing learning in the 2013 curriculum requires the ability of teachers in the IT field, especially in making learning media easy and interesting because learning in the 2013 curriculum consists of observing, asking, reasoning, trying and communicating. The assessment conducted in the 2013 curriculum includes three domains, namely affective, cognitive, and psychomotor. The purpose of community service is to provide assistance in making media powtoon learning in the thematic 2013 curriculum learning for class V of the Cluster 1 Elementary School in Bogor City. This assistance gets a positive response as evidenced by the enthusiasm of the teacher in following from beginning to finish. Although this mentoring training is different from usual, using online media or webinars because of Covid-19. When giving material about the introduction of the Powtoon program, the teachers learned a lot, because this program was a new program. The enthusiasm and readiness of the teachers signifies motivation to foster student activity in learning.